Pengaruh Price Discount, Visual Merchandising dan Positive Emotion terhadap Impulse Buying di Ramayana Department Store Yogyakarta - Arista Natia Afriany; Adi Kurniawan; Anindita Imam Basri (Jurnal Bisnis dan Ekonomi, 2021)
This study aims to determine the effect of price discount, visual merchandising, and positive emotion on impulse buying at Ramayana Department Store Yogyakarta. The study was conducted in the Special Region of Yogyakarta. the sample in this study was 80 respondents and used a non-probability sampling technique with a purposive sampling method. The data analysis technique used multiple linear regression analysis, T test (partial), F test (together), coefficient of determination (R2). The results of the effect proved that, price discount had positive and insignificant effect as evidenced with a regression coefficient value of 0.138 and sig. 0.015, visual merchandising had positive and insignificant effect as evidenced with a regression coefficient value of 0.199 and sig. 0.025, and positive emotion had positive and insignificant effect as evidenced with a regression coefficient value of 0.455 and sig. 0.001. The result of the effect of the three variables, they together have an effect on impulse buying with a significant 0.000< 0.05. The coefficient of determination in this research 34.2%.